Combined Effects of Insulation Thickness and Wire Curvature Radius on Maximum Electric Field Intensity for Domestic Wires (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
The electric field intensity is influenced by several factors, including the thickness of the dielectric material and the magnitude of the applied voltage. In scenarios involving curved wires or cables, the radius of curvature plays a significant role in determining the electric field intensity. To minimize the need for conducting numerous experiments or simulations to ascertain the maximum electric field intensity under varying conditions, a mathematical model can be employed. This paper discusses findings related to how insulation thickness and wire curvature radius impact electric field intensity within PVC curved wire configurations commonly utilized in domestic installations. The geometric configuration of these PVC curved wires was modelled using Finite Element Analysis (FEA) software (COMSOL Multiphysics). The simulation involved varying the insulation thickness between 0.6 mm and 1.0 mm, and the wire curvature radius from 0.4 mm up to 0.7 mm. The findings indicate that multi-linear regression model is suitable to predict maximum electric field intensity as a function of insulation thickness and wire curvature radius at a prediction error of 1% up to 3%.